2016
DOI: 10.1007/s10545-016-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the functional muscle–bone unit of the forearm in patients with phenylketonuria by peripheral quantitative computed tomography

Abstract: Bone disease in patients with phenylketonuria (PKU) is incompletely characterized. We therefore analyzed, in a cross-sectional study radius macroscopic bone architecture and forearm muscle size by peripheral quantitative computed tomography (pQCT) and muscle strength by hand dynamometry in a large cohort (n = 56) of adolescent and adult patients with PKU aged 26.0 ± 8.9 (range, 11.8-41.5) years. Data were compared with a reference population (n = 700) from the DONALD study using identical methodology. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…This lack of difference may reflect the 3-wk GMP-MF treatment being too short and/or the PKU genotype as the predominant driver of elevated cytokine concentrations. Second, bone-muscle functional interactions demonstrate that reduced lean mass or muscular abnormalities can contribute to bone resorption, reduced bone strength, and increased risk for fracture [6, 18]. For example, in healthy young adults at bedrest, a high dietary acid load induced by AA supplementation increased urinary markers of bone resorption (NTX and deoxypyridinoline) and calcium excretion [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of difference may reflect the 3-wk GMP-MF treatment being too short and/or the PKU genotype as the predominant driver of elevated cytokine concentrations. Second, bone-muscle functional interactions demonstrate that reduced lean mass or muscular abnormalities can contribute to bone resorption, reduced bone strength, and increased risk for fracture [6, 18]. For example, in healthy young adults at bedrest, a high dietary acid load induced by AA supplementation increased urinary markers of bone resorption (NTX and deoxypyridinoline) and calcium excretion [18].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal fragility, characterized by low bone mineral density (BMD) and increased fracture risk, has emerged as a poorly understood chronic complication of PKU managed with AA-MF [46]. There is no consensus on the incidence, etiology, implications, and risk factors for low BMD in PKU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen et al [2] state that the fracture prevalence in our population is twice as high as that reported in other studies, referring to Choukair et al [4] report that 24/56 patients (43%) have had a fracture at least once in their lifetime. Importantly, this is comparable to the percentage reported by us [1], even though they describe a population with mainly adult patients.…”
Section: Dear Editorsmentioning
confidence: 50%
“…Two recent studies described fractures in PKU. In a cross-sectional study [5], it is indicated that 43% of 56 PKU patients aged 12-42 sustained fractures. According to a systematic review [6], clinical fractures affected 20% (53 of 263) of PKU patients across 6 studies.…”
Section: Dear Editorsmentioning
confidence: 99%